Studi Pelaksanaan Praktikum IPA dan Biologi Sekolah Menengah selama Masa Pandemi COVID-19 - Putri Agustina (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Biology learning in accordance with its essence should emphasize direct experience so that students areable to explore the natural surroundings scientifically. Practicum is a vehicle to provide directexperience to students. However, due to the COVID-19 pandemic and the implementation of distancelearning, the implementation of the practicum cannot run as it should. The purpose of this study was todescribe the implementation of Biology/Science practicum in secondary schools during the COVID-19pandemic T.A 2020/2021. This research is a descriptive study that was conducted from February to July2021. The subjects of this research were Biology and Science teachers in high schools throughout SoloRaya. The data was taken by using a questionnaire technique which was distributed through googleform. The number of respondents in this study were 41 people. The results of the questionnaire analysison the implementation of Biology and Science practicums in high schools throughout Solo during theCOVID-19 pandemic, it was found that 65.9% carried out practicums during the COVID-19 pandemicwhile 34.1% did not carry out practicums. The implementation of the practicum uses various platformssuch as google meet and moodle app, zoom meeting and youtube, google classroom, and so on.Regarding the effectiveness of online practicum implementation, 92.7% said it was not effective while7.3% said it was effective